Serum soluble (pro)renin receptor level as a prognostic factor in patients undergoing maintenance hemodialysis - Yoshifumi Amari (Nature Portfolio, 2021)
Abstract The (pro)renin receptor [(P)RR)] is a multifunctional protein that is cleaved to generate the soluble (P)RR [s(P)RR], reflecting the status of the tissue renin-angiotensin system and/or activity of the (P)RR. The serum s(P)RR level is associated with arteriosclerosis, independent of other risk factors, in patients undergoing hemodialysis (HD). This study was conducted to investigate whether the s(P)RR level was associated with new-onset cardiovascular events or malignant diseases and poor prognosis in patients undergoing HD. Overall, 258 patients [70 (61–76) years, 146 males] undergoing maintenance HD were prospectively followed up for 60 months. We investigated the relationships between s(P)RR levels and new-onset cardiovascular events/ malignant diseases and mortality during the follow-up period using Cox proportional hazard analyses. The cumulative incidence of new-onset cardiovascular events (P = 0.009) and deaths (P < 0.001), but not of malignant diseases, was significantly greater in patients with higher serum s(P)RR level (≥ 29.8 ng/ml) than in those with lower s(P)RR level (< 29.8 ng/ml). A high serum s(P)RR level was independently correlated with cardiovascular mortality (95% CI 1.001–1.083, P = 0.046). The serum s(P)RR level was associated with cardiovascular events and mortality, thus qualifying as a biomarker for identifying patients requiring intensive care.